(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This study assesses the possible use of local raw materials (clays) for producing expanded clay pellets and test the product with American standard for test materials (ASTM) and according to ASTM C 330.For using them as lightweight aggregate in different construction applications, like thermal insulation, lightweight structural concrete , decoration pieces ,etc. The clay was collected from Al-Anbar province. The clay was bloated at 1150 C° without adding any impurities ,just mechanical treatment and perfect firing program, in order to obtain good bloating coefficient that is related with firing parameters (access time, temperature, socking time). We got the results of the match determined by the American specification (ASTM C330) and in which is considered lightweight aggregate. We got density about (280 kg / m3) which is much less than that determined by ASTM where the aggregate lightly if the density is less than (880 kg / m3).